Research of Inverse Solution of Manipulator based on Beetle Antennae Search and Differential Evolution - Xiaolong Shen; Jifang Wang (Jixie chuandong)
In order to simplify the solution method of inverse kinematics of the manipulator， improve the accuracy of the solution， and enhance the universality of the method， the intelligent optimization algorithms are used to turn the inverse kinematic solution into an optimization problem. Firstly， the objective function of the end pose error according to the positive kinematic equation is established， and the best flexibility and energy consumption constraints to construct the fitness function are combined so that the manipulator has the best flexibility and lower energy consumption when meeting the requirements of the pose error； In order to unify the accuracy of position and attitude convergence and control the evolution direction， the pose balance coefficient and the pose error adjustment coefficient are introduced； Then， the individual optimization of the beetle search with excellent performance in group optimization is integrated with the differential evolution algorithm， so as to improve the convergence accuracy and speed of the algorithm； Finally， inverse solution experiments are conducted on the 6R manipulator and the redundant manipulator. The results show that the proposed algorithm has high convergence accuracy， a fast speed and a good versatility.